ANALISIS BIAYA PENEBANGAN PADA HUTAN JATI RAKYAT DI KABUPATEN BONE - A. Mujetahid M. (Forestry Faculty of Universitas Hasanuddin, 2010)
Community teak forest in Bone Regency was +- 4,220 ha in wide, spreading in Amali, Ulaweng, Bengo, Mare, Tonra, Kahu, Salomekko, Ajangale, Dua Boccoe, Lamuru, Tellulimpoe, Lappariaja, Libureng, Palakka, Bontocani and Ponre Subdistricts. The descriptive method was used to describe and clarify felling activities of community teak forest yield. The quantitative approach was conducted by recording and analyzing the data such as potency, length, diameter, volume, working time, productivity, cost, etc. The study was aimed to felling cost m-3 with self-management was cheaper than by the piece, namely Rp.298,712,8 and Rp. 471,159.90 with difference amounting of Rp 172,447.10 m-3, but collector-traders chose contract work because considering social aspect, chance and opportunity to get others teak. Key words: community teak forest, felling, cost.